Development of Design Digital Application System for Laundry Partner Services: A Smart Village Initiative - Nicholas Napitupulu; Farel Fazriel Marbella; Stevan Agustin Purba; Hanif Rasendra; Anindo Saka Fitri (International Journal of Computer, Network Security and Information System, 2026)
The development of smart village concepts promotes the use of digital technology to enhance laundry service efficiency at the village level. This paper outlines the development of a digital application system addressing manual challenges such as stock recording, payments, and garment tracking at partner laundry managed by Virna Indri Luthfia. The system supports customer management, orders, payments, and real-time reporting via mobile features for customers, partners, and admins.